PELATIHAN KELOMPOK USAHA PASTEL MINI DESA PANDAU JAYA MELALUI DIVERSIFIKASI DAN FORTIFIKASI UDANG - Simanjuntak, Jan Stepfely; Sukmiwati, Mery; Leksono, Tjipto; Herdini, Herdini; Syawal, Henni; Azizah, Afra; Farrand Noor, Andi Almer; Yovanie, Faira; Nabila, Febi; Fazira, Meisya Amanda; Farkhan, Mochammad; Nabellia, Nabellia; Salsabila Hendri, Putri Noviayu; Anugrah, Rio Persal (Jurnal Sinergitas PKM & CSR, 2022)
Diversification and fortification are efforts that can be made in increasing the value of food quality in terms of increasing product varieties and adding product nutritional value through the addition of food ingredients, one example of this product is fish or shrimp. The purpose of this service is to provide training on CPPB-IRT, technology transfer for mini pastel product processing, labeling, mini pastel training SOPs, product packaging and label design, and website creation, Facebook, Instagram (information and promotions) as well as making fish/shrimp flavours on mini pastels. The method of implementation that would be carried out in this activity was in the form of education, with the method of lectures, discussions, demonstrations and evaluation of product processing/manufacturing techniques for mini pastel businesses. Targets and outcomes to be achieved from community service activities, namely mini pastel products sold to the market must meet product specifications in accordance with SNI 7388: 2009. Packaging and labeling were in accordance with food packaging standardization PP No. 69 of 1999, standard operating procedures for guarantees quality of mini pastels. Based on the results obtained, the responses from the owners and employees of the mini pastel business group were quite enthusiastic in participating in the counseling activities.abtract in bahasaDiversifikasi dan fortifikasi merupakan upaya yang dapat dilakukan dalam meningkatkan nilai mutu pangan dalam hal peningkatan varietas produk dan penambahan nilai gizi produk melalui penambahan bahan pangan, salah satu contoh produk ini adalah ikan atau udang. Tujuan pengabdian ini adalah memberikan pelatihan CPPB-IRT, alih teknologi pengolahan produk mini pastel, pelabelan, SOP pelatihan mini pastel, desain kemasan dan label produk, dan pembuatan website, facebook, instagram (informasi dan promosi) serta membuat rasa ikan/udang di mini pastel. Metode pelaksanaan yang akan dilakukan dalam kegiatan ini berupa edukasi, dengan metode ceramah, diskusi, demonstrasi dan evaluasi teknik pengolahan/pembuatan produk untuk usaha mini pastel. Sasaran dan hasil yang ingin dicapai dari kegiatan pengabdian kepada masyarakat yaitu produk mini pastel yang dijual ke pasaran harus memenuhi spesifikasi produk sesuai dengan SNI 7388 : 2009. Pengemasan dan pelabelan sudah sesuai dengan standarisasi kemasan pangan PP No. 69 Tahun 1999, standar operasional prosedur untuk menjamin kualitas mini pastel. Berdasarkan hasil yang diperoleh, respon dari pemilik dan karyawan cukup antusias mengikuti kegiatan penyuluhan.